PENGARUH LATIHAN SMALL SIDED GAMES TERHADAP KETEPATAN PASSING BAWAH SISWA EKSTRAKURIKULER BOLA VOLI DI SMA NEGERI 10 TANJUNG JABUNG TIMUR - Doni Rianto; Ugi Nugraha; Alek Oktadinata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of small-sided games training on the underhand passing accuracy of volleyball extracurricular participants at SMA Negeri 10 Tanjung Jabung Timur. The study employed an experimental method using a One-Group Pretest–Posttest Design. The sample consisted of 14 volleyball extracurricular participants selected through total sampling. Data were collected using an underhand passing accuracy test and analyzed through the Shapiro–Wilk normality test and the Paired Sample t-test. The results showed that the mean pretest score was 17.14, while the mean posttest score increased to 25.57, indicating an improvement of 8.43 points or 49.10%. The normality test revealed that both pretest and posttest data were normally distributed, with significance values of 0.654 and 0.229, respectively (p > 0.05). The hypothesis test results showed that the calculated t-value (11.640) was higher than the t-table value (2.160) at the 0.05 significance level. Therefore, the research hypothesis was accepted. It can be concluded that small-sided games training has a significant effect on improving underhand passing accuracy in volleyball among extracurricular participants at SMA Negeri 10 Tanjung Jabung Timur.